2020
DOI: 10.17323/jle.2020.10846
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence on the Effectiveness of the Learning by Teaching Technique among University-level English as a Foreign Language Students

Abstract: Learning via teaching has been accepted as one of the best ways to achieve a deep understanding of a topic. This research was aimed at seeking scientific evidence to support this claim by comparing the scores the university-level EFL students obtained through the learning by teaching technique and those obtained by students who were taught traditionally using a teacher-centered approach. The experimental group consisted of 22 students who were taught pedagogical content knowledge, i.e. English Language Testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…141-142). The not-large enough sample sizes contribute to, among others, conflicting results in similar research studies such as the study about the strength of the relationship between the use of metacognitive language-learning strategies and language-learning motivation by Wu (2007) and Goh and Foong (1997), and the empirical evidence on the effect of learning by teaching technique by Kasim, Muslem, and Mustafa (2020). Another example is differences in effect sizes of peer-assessment across 54 published research found by Double et al (2019) because they did not consider sample sizes in selecting papers to be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…141-142). The not-large enough sample sizes contribute to, among others, conflicting results in similar research studies such as the study about the strength of the relationship between the use of metacognitive language-learning strategies and language-learning motivation by Wu (2007) and Goh and Foong (1997), and the empirical evidence on the effect of learning by teaching technique by Kasim, Muslem, and Mustafa (2020). Another example is differences in effect sizes of peer-assessment across 54 published research found by Double et al (2019) because they did not consider sample sizes in selecting papers to be analyzed.…”
Section: Introductionmentioning
confidence: 99%